Tackling men's violence in families Nordic issues and dilemmas - Eriksson, Maria 1969- (Policy Press, 2005)
Nordic countries are generally regarded as global welfare role models. Consequently, the influence of Nordic welfare systems in academic and policy debates has been immense. By focusing on the vital issue of violence by men to female partners and/or their children, this book seeks to reconsider this over-simplistic image
Title from publisher's bibliographic system (viewed on 20 Jan 2022)
Keywords: Family violence / Scandinavia; Abused women / Services for / Scandinavia